NOL-7 serves as a potential prognostic-related biomarker for hepatocellular carcinoma - Qiucheng Lei; Yingchun Huang; Feiwen Deng; Huazhen Zheng; Xitao Hong; Peng Wang; Jin Lv; Huanwei Chen; Zhenling Ji (Discover Oncology)
Abstract Background Nucleolar protein 7 (NOL7), a specific protein found in the nucleolus, is crucial for maintaining cell division and proliferation. While the involvement of NOL7 in influencing the unfavorable prognosis of metastatic melanoma has been reported, its significance in predicting the prognosis of patients with Hepatocellular Carcinoma (HCC) remains unclear. Methods Aberrant expression of NOL7 in HCC and its prognostic value were evaluated using multiple databases, including TCGA, GTEx, Xiantao Academic, HCCDB, UALCAN, TISCH, and STRING. Immunohistochemistry (IHC) and quantitative real-time PCR were used to validate NOL7 expression levels in patients with HCC. Results NOL7 expression was higher in the HCC samples than in the normal samples (P < 0.05). NOL7 was strongly associated with elevated AFP levels, vascular invasion, TNM stage, poorer tumor differentiation, and poorer survival (all P < 0.05). Elevated NOL7 expression correlated with decreased overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI) (all P < 0.05). Multivariate analysis revealed that NOL7 was an independent prognostic factor that was significantly related to OS and DSS. The nomogram showed a good predictive performance based on the calibration plot. In addition, NOL7 expression was significantly correlated with cell cycle modulators, immune checkpoints, and various immune cell populations. In addition, we identified eight potential pathways associated with NOL7 as the most promising pathways for NOL7 in HCC. Low-risk specimens were more sensitive to oxaliplatin, cisplatin, irinotecan, sorafenib, and cytarabine than high-risk specimens. Conclusion NOL7 may serve as a potential biomarker for predicting clinical outcomes and may provide guidance for clinical therapy in patients with HCC.